Effect of Bacterial Pneumonia on Lung Simian Immunodeficiency Virus (SIV) Replication in Alcohol Consuming SIV‐Infected Rhesus Macaques. (15th February 2013) - Nelson, Steve; Happel, Kyle I.; Zhang, Ping; Myers, Leann; Dufour, Jason P.; Bagby, Gregory J.
<x xml:space="preserve">Abstract</x> Background Opportunistic infections in human immunodeficiency virus (HIV)‐infected persons have been shown to increase the rate of HIV replication. In populations where prophylaxis against Pneumocystis pneumonia is utilized, bacterial pneumonia is now the leading cause of lower respiratory tract infection in HIV+ patients. Our prior studies have shown that chronic alcohol consumption in demarcated simian immunodeficiency virus (SIV)‐infected rhesus macaques increases plasma viral load set point and accelerates progression to end‐stage acquired immune deficiency syndrome. While chronic alcohol abuse is well known to increase the incidence and severity of bacterial pneumonia, the impact of alcohol consumption on local and systemic SIV/HIV burden during lung infection is unknown. Therefore, we utilized the macaque SIV infection model to examine the effect of chronic ethanol (EtOH) feeding on SIV burden during the course of pulmonary infection with Streptococcus pneumoniae, the most commonly identified etiology of bacterial pneumonia in HIV+ and HIV− persons in developed countries. Methods Alcohol was administered starting 3 months before SIVmac251 inoculation to the end of the study via an indwelling intragastric catheter to achieve a plasma alcohol concentration of 50 to 60 mM. Control animals received isocaloric sucrose. Four months after SIV infection, the right lung was inoculated with 2 × 106 CFU S. pneumoniae. Results Leukocyte recruitment into the lung, pulmonary bacterial clearance, and clinical course were similar between EtOH and control groups. While plasma SIV viral load was similar between groups postpneumonia, chronic EtOH‐fed macaques showed a prolonged increase in SIV RNA in bronchoalveolar lavage fluid. Alveolar macrophages isolated from EtOH‐fed macaques 1 day post‐pneumonia showed greater nuclear factor kappa beta (NF‐κB) activation. Conclusions This study indicates that chronic EtOH feeding results in enhanced local, but not systemic, SIV replication following pneumococcal pneumonia. Increased NF‐κB activity in the setting of chronic EtOH ingestion may play a mechanistic role in this observation.